Persepsi Siswa Kelas XI Tentang Program Full Day School (Sekolah Sehari Penuh) di SMA Negeri 2 Sawahlunto - Negoro, R. Ady - (STKIP PGRI Sumbar, 2014)
The research have purpose for to know and analayze how to student perception class XI about full day school programme in senior high school 2 Sawahlunto to observe from motivation aspect and interest student. This research to classify in qualitie research. This informan about research to take from purposive sampling and the informan in the research is the student of class XI senior high school 2 Sawahlunto to show the first student and the students. In the result in freid: 1) full day school programme done in senoir high school 2 Sawahlunto very useful likes get to know leclge, and then the student can get memorite the last lesson. The parents, the teacher and colleague give motivation. Like sugest for study hard and the parents prepare breakfast and their necessang so from their motivation is give bring into their ideal, and the next level school. 2) during do programme full day school, the students feel happy and unhappy. The student can be happy if the implementation great with other people, add kown ledge and can develop their talent their se if like sport, act and other lesson. The student can be unhappy like some teacher nervous say their lesson, the theacher still focus to lesson book and then donât enough facility and school necessary can make full day school activity not be durring activity. The parent, the teacher and colleague for give motivation and is hoped for necessary school in the school be prefect .